E-Government Dalam Bingkai Reformasi Administrasi Publik Menuju Good Governance - Junaidi, Junaidi (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2005)
Need for reform in public sector should become leverage point for reform of public administration. Implementation process ofpublic administrative reform is not easy task It needs clear and directive concept related to target, strategy, approach or model selected The concepts require tools allowing them implemented easily, accessible by many people, quick, inexpensive and convenient. So, e-government may be said as the most appropriate solution. Author argues that efforts to develop e-government in public administration should be placed in true context; that is, development of e-government should be viewed as tool to accelerate implementation of public administrative reform in order to realize good governance. This paper content contain model of e-government development in context ofpublic administrative reform toward good governance. In the last part, author gives recommendation for central and local government that will develop e-government: development of e-government should be done with clear concept of e-government development related to target and strategy or approach written in a blue print or in term of lnpres No.3/2003, strategic plan of e-government, which is established considering rationality aspect and democratic process.